2015
DOI: 10.17239/l1esll-2015.15.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Writing education and assessment in Norway: Towards shared understanding, shared language and shared responsibility

Abstract: This article reports on a study of writing and assessment in upper primary school, focusing on how teachers develop assessment competence through professional discussions in interdisciplinary groups. The empirical data consist of dialogues between teachers assessing and giving feedback on students' texts from different subjects. To support their evaluations, the teachers used and referred to a defined construct of writing and norms for expected writing proficiency. The analyses reveal a complex picture of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
2
12
0
5
Order By: Relevance
“…This includes rater background (Leckie & Baird, 2011;Lim, 2011), rater cognition (Baker, 2012;Eckes, 2012;Zhang, 2016), and rater values and expectations (Baker, 2010). For example, studies have shown a general lack of grammatical metalanguage among teachers, making it difficult both for students to learn to write (Myhill, Jones, & Watson, 2013) and for teachers to discuss and assess student texts (e.g., Matre & Solheim, 2015, 2016. Research on rater decision-making has revealed a tendency for raters to pay insufficient attention to the common framework with which they are presented and to value more highly their own, individually held, and often tacit assessment practices (e.g., Wyatt-Smith, Klenowski, & Gunn, 2010;Jølle, 2014).…”
Section: Interpretive Communitiesmentioning
confidence: 99%
“…This includes rater background (Leckie & Baird, 2011;Lim, 2011), rater cognition (Baker, 2012;Eckes, 2012;Zhang, 2016), and rater values and expectations (Baker, 2010). For example, studies have shown a general lack of grammatical metalanguage among teachers, making it difficult both for students to learn to write (Myhill, Jones, & Watson, 2013) and for teachers to discuss and assess student texts (e.g., Matre & Solheim, 2015, 2016. Research on rater decision-making has revealed a tendency for raters to pay insufficient attention to the common framework with which they are presented and to value more highly their own, individually held, and often tacit assessment practices (e.g., Wyatt-Smith, Klenowski, & Gunn, 2010;Jølle, 2014).…”
Section: Interpretive Communitiesmentioning
confidence: 99%
“…However, this framework and these labels were chosen to highlight the starting phase of writing, not to cover all the purposes a text can serve at different stages of the process. Our understanding is therefore narrower, for instance, than the one defined in the wheel of writing as knowledge development and exchange of information (Matre & Solheim, ) or understood in context as the intention behind an action (Halliday & Matthiessen, ).…”
Section: Discussionmentioning
confidence: 97%
“…Ett exempel på detta är det norska NORM-projektet (Berge, Skar, Matre, Solheim, Evensen et al, 2017). Här visas att lärares bedömningar fördjupas när de har tillgång till gemensamma bedömningsnormer baserade i ett professionellt metaspråk (Matre & Solheim, 2015). Men inte heller i de sju värderingsområden som utgör normer inom NORM-projektet lyfts några berättartekniska aspekter fram.…”
Section: Tidigare Forskningunclassified